2020
DOI: 10.3892/ol.2020.11836
|View full text |Cite
|
Sign up to set email alerts
|

Expression and clinical significance of methyl‑CpG binding domain protein 2 in high‑grade serous ovarian cancer

Abstract: Platinum resistance is an important cause of clinical recurrence and mortality of patients with high-grade serous ovarian cancer (HGSOC). Methyl-CpG binding domain protein 2 (MBD2) serves an important role in tumor progression; however, its role in HGSOC remains unclear. The aim of the present study was to investigate the expression of MBD2 in HGSOC and its role in drug resistance and prognosis of HGSOC. MBD2 expression was analyzed by immunohistochemical staining and western blotting. The associations between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 53 publications
0
5
0
Order By: Relevance
“…by binding to its promoter in leukemic cells Previous studies have shown that MBD2 functions as a "reader" of DNA methylation and translates methylated DNA into signals for transcriptional silencing [9,11,19,20]. Therefore, we reasoned that the transcript levels of CDKIs might be consequently restored after the loss of MBD2.…”
Section: Mbd2 Suppresses the Transcriptional Expression Of Cdkn1cmentioning
confidence: 97%
See 1 more Smart Citation
“…by binding to its promoter in leukemic cells Previous studies have shown that MBD2 functions as a "reader" of DNA methylation and translates methylated DNA into signals for transcriptional silencing [9,11,19,20]. Therefore, we reasoned that the transcript levels of CDKIs might be consequently restored after the loss of MBD2.…”
Section: Mbd2 Suppresses the Transcriptional Expression Of Cdkn1cmentioning
confidence: 97%
“…MBD2 also has cell-and tissue-specific functions that are context-dependent [8]. Many studies have demonstrated that MBD2 might bind to hypermethylated promoters of tumor suppressor genes and contribute to their transcriptional silencing in multiple tumors, such as ovarian cancer [9], renal cell carcinoma [10], and hepatocellular carcinoma [11]. Our previous study also showed that MBD2 acts as a tumor suppressor in T cell acute lymphoblastic leukemia (T-ALL) lymphomagenesis in murine experiments [12].…”
Section: Introductionmentioning
confidence: 97%
“…After positively stained cells count and background evaluation, semi-quantitative P4HA2 expression analysis by IHC was evaluated using a staining score, as Gong et al previously described. 12 The established staining score (range, 0–7) was the sum of staining intensity and proportion of positively stained cells. A final score of 0–4 points indicated no or low expression, and 5–7 points indicated high expression.…”
Section: Methodsmentioning
confidence: 99%
“…In ischemic insults, the essential endothelial genes such as eNOS and VEGFR 2 undergo a DNA methylation turnover, and MBD2 reads DNA methylation changes signals for mediating gene silencing ( Rao et al, 2011 ). MBD2 overexpression has been detected in various solid tumors and promotes cancer progression by mediating silencing of tumor suppressor genes ( Gong et al, 2020 ). MBD2 binds to the gene promoter of brain angiogenesis inhibitor 1 (BAI1) and inhibits its antiangiogenic and antitumorigenic properties in glioma cells.…”
Section: Epigenetic Control Of Angiogenesis In Tumor Developmentmentioning
confidence: 99%